Society 5.0: A Bibliometric Analysis from Management Approach - Mahat, Dipak (NPRC Journal of Multidisciplinary Research, 2024)
The Goals of Society 5.0 provided an innovative viewpoint on the function and significance of technological advancement in resolving contemporary social issues in contemporary society, In light of this, the researcher attempted to determine the current publication status of Society 5.0 within the field of management. The researcher applied bibliometric analysis to examine a total of 125 documents that were published within a span of five years. The findings revealed four distinct clusters that base on the themes of framework, understanding society 5.0, utilization of society 5.0, and challenges. The co-authorship network among Russia, Italy, and the United States is mostly impressive. Future studies should incorporate edited books, chapters, and monographs to boost Society 5.0's bibliometric analysis. Include all Society 5.0-related fields.